Inflation, Quarterly Balance Sheets and the Possibility of Fraud: Benford's Law and the Brazilian Case - Gava, Alexandre M.; Vitiello, Luiz (JABM, 2014)
We investigate whether changes on inflation levels have an impact on the possible instance of fraud in financial statements. By assuming that Benford's law can properly capture the frequency of occurrence of the first digit of figures in financial statements of Brazilian companies, we applied it to 1,259 quarterly balance sheets from 1986 to 2009, period which contains high inflation (prior to 1994) and low inflation (after 1994). Whilst it has been suggested that Benford's law works better when the data cover many orders of magnitude, results for the aggregate data show that the low inflation period fits better to Benford's law than the high inflation period. We also divide our sample by quarters but the analysis show no significant difference between them. These results may be explained by the abolition of inflationary adjustments to financial statements in 1995, which increased the transparency of the balance sheets during the low inflation period.